ANALISIS KEJADIAN PREMENSTRUASI SINDROM (PMS) PADA MAHASISWI - Winedhar Prawestri; Mira Triharini; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2014)
Premenstrual syndrome (PMS) is a physical and psychological symptoms that occurs at 7 to 10 days before menstruationand disappear during menstruation. There are many factors that associated with the incident of PMS stress, diet, andphysical activity. This study aimed to analyze factors correlating with PMS incident to female student’s in Facultyof Nursing Airlangga University. Design used in this study was cross sectional design. The population was all A2011female students, Faculty of Nursing, Airlangga University. Total sample was 70 respondents, taken according to inclusioncriteria. The independent variables in this research include stress, diet, and physical activity. The dependent variable inthis research was the incident of PMS. Data were taken by questionnaire and were analyzed using binary regressionlinear test. Results showed that stress has parcially correlation with PMS (t= 1,999<4,838). Meanwhile diet and physicalactivity parcially has no correlation with PMS. Based on F score, stress, diet, and physical activity has no correlation withPMS (F= 2,094<3158). It can be concluded that stress on A2011 female students has correlation with incident of PMS.Further studies should involve larger respondents and better measurement tools to obtain more acute results.